Broadening Our Portfolio in the Genetic Improvement of Maize Chemical Composition. Issue 8 (August 2016) - Wen, Weiwei; Brotman, Yariv; Willmitzer, Lothar; Yan, Jianbing; Fernie, Alisdair R.
Abstract : The adoption of recombinant inbred line and introgression line populations, as well as the study of association mapping panels, has greatly accelerated our ability to identify the genes underlying plant phenotypic variance. In tandem, the development of metabolomics approaches has greatly enhanced our ability to comprehensively define cellular chemical composition. As a consequence, breeding for chemical composition is being extended beyond our traditional targets of oil and protein to include components such as essential amino acids, vitamins, and antioxidant secondary metabolites with considerable purported consequences for human health. Here, we review the above-mentioned developments paying particular attention to the genetic architecture of metabolic traits as well as updating the perspective for utilizing metabolomics in maize improvement. Trends: Extensive breeding resources are currently available for maize. Concurrently, our capacity for evaluating chemical composition of plants has greatly increased given the advent of metabolomics. Taken together, these advances allow us to extend our portfolio for compositional quality oriented breeding.